SISTEM INFORMASI PROGRAM CSR BIDANG PENDIDIKAN SEBAGAI UPAYA PENGEMBANGAN MASYARAKAT DI MALANG - Latifah, Sri Wahjuni (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Research on information systems education CSR programs as community development efforts on the Hapless was carried out with the aim of identifying characteristics of recipients offunding programs, community access capability mengentahui against the program, identifying the components of the information system of funding programs that subsequently is used as information to devisestrategies for community development. The data obtained by questionnaire andinterviews to spread the recipient Fund programme and Fund Manager at Universities in Malang. Further data were analyzed with a qualitative approach. The results showed that in general the sources of funding programs can be groupedinto three, from the Government, private companies and public companies. So, effective access to information to obtain scholarshipsmore sourced information traditionally. While the funding of information system components include a set of inputs, processes and outputs. So far this programutilization varies as to support skill development study costs, as well as to the cost of living. Based on the SWOT analysis can be formulated the strategy of community development through the establishment of PPM-Entrepreneurship in each area with the direct involvement of the recipient of the funding program.